Eolic potentials in Moa's region, Cuba - Terrero-Matos, Eduardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2008)
The paper work shows some of the preliminary results in relation on the Moa region where the behavior of the eolic potencial of the Cuba Northeast region is characterized. These results convey to the selection of places where studies of factual eolic energy can be done.